Usefulness of Previous Methicillin-resistant Staphylococcus aureus Screening Results in Guiding Empirical Therapy for S Aureus Bacteremia - Anthony D Bai; Lisa Burry; Adrienne Showler; Marilyn Steinberg; Daniel Ricciuto; Tania Fernandes; Anna Chiu; Sumit Raybardhan; George A Tomlinson; Chaim M Bell; Andrew M Morris (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Staphylococcus aureus bacteremia (SAB) is an important infection. Methicillin-resistant S aureus (MRSA) screening is performed on hospitalized patients for infection control purposes.